"Comrades, Let's March!". The Revolution of 1905 and its impact on financial markets. (28th September 2017) - Opitz, Alexander
Abstract: This paper examines the impact of the Revolution of 1905 on contemporary capital markets by applying an event study on Russian sovereign bonds. The landmark in Russian history comprised violent protests, resulting in the introduction of a parliament and the adoption of a constitution. While this was appreciated by investors, related events and the associated political and economic uncertainty—combined with large financial pressure—resulted in a negative securities market reaction. Further, the Russo-Japanese War, closely linked with the revolutionary events, is considered. Consistent with the established literature, war-related events did not always translate into price reactions. In addition to Berlin, the paper examines the Saint Petersburg Stock Exchange. The results suggest that the two markets were already well integrated at the turn of the 20th century.